2020
DOI: 10.3390/w12082099
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Surface Runoff on the Yamal Peninsula, Russia, Using ERA5 Reanalysis

Abstract: The Yamal peninsula is a territory of active industrial development as it contains several rich fields of natural condensed gas and oil. The density of the gullies net on the Yamal peninsula is one of the highest in the Russian Arctic. The natural environment or constructions can be potentially damaged by gully erosion and the cost of such damage is high. The models of gully erosion require surface runoff estimates. The hydrological model was developed for surface runoff estimation during the spring snow thaw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Many recent studies have used ERA5 for many hydrological applications. These include modeling of global mean P (Hersbach et al, 2018), evaluating daily P products over the continental United States (Beck et al, 2019a), modelling of surface runoff (Matveeva & Sidorchuk, 2020), and catchment scale hydrological modelling (Tarek et al, 2020). The dataset can be obtained at https://cds.climate.copernicus.eu/.…”
Section: Era5mentioning
confidence: 99%
“…Many recent studies have used ERA5 for many hydrological applications. These include modeling of global mean P (Hersbach et al, 2018), evaluating daily P products over the continental United States (Beck et al, 2019a), modelling of surface runoff (Matveeva & Sidorchuk, 2020), and catchment scale hydrological modelling (Tarek et al, 2020). The dataset can be obtained at https://cds.climate.copernicus.eu/.…”
Section: Era5mentioning
confidence: 99%
“…Wang et al [57], Liu et al [58], Hersbach et al [59], Terzago et al [60], and Orsolini et al [61] conducted a comprehensive assessment of snow cover parameters for this dataset, the findings showed that the ERA5 dataset can well capture the spatial distribution of snow cover and a wide range of characteristics of seasonal changes despite its large positive bias. Wang et al [62], Matveeva and Sidorchuk [63], and Yılmaz et al [64]…”
Section: Data 221 Snow Datamentioning
confidence: 99%
“…Probability density functions of runoff depth for a small catchment can often be approximated with an exponential relationship [27]. For this case, E TPi in Equation ( 31) is an inverse power-law function of M cr .…”
Section: Express Estimation Of Gully Erosion Riskmentioning
confidence: 99%
“…Meteorological information, in form of changing through time air temperature and precipitation, was taken from ERA5 reanalysis. The sequences of surface runoff depths were calculated with the hydrological model, validated on the hydrological measurements on the selected catchment [27].…”
Section: Gultem Model Validation and Calibrationmentioning
confidence: 99%
See 1 more Smart Citation